Occurrences of triatomines (Hemiptera: Reduviidae) and first reports of Panstrongylus geniculatus in urban environments in the city of Sao Paulo, Brazil - Ceretti-Junior, Walter; Vendrami, Daniel Pagotto; Matos-Junior, Marco Otavio de; Rimoldi-Ribeiro, Aline; Alvarez, Julia Vono; Marques, Sandro; Duarte, Agnaldo Nepomuceno; Silva, Rubens Antonio da; Rosa, Joao Aristeu da [UNESP]; Marrelli, Mauro Toledo (Inst Medicina Tropical Sao Paulo, 2018)
This note reports on occurrences of triatomine species in the city of Sao Paulo, Brazil, registered between 1988 and 2017. Records of triatomines captured in Sao Paulo are based on specimens received spontaneously from Health Surveillance Centers, Health Centers and Zoonosis Control Centers in the city as well as from citizens. Species were identified morphologically at the Public Health Entomology Laboratory, Faculty of Public Health, University of Sao Paulo, where the triatomines, which are vectors of Chagas disease, were tested for Trypanosoma cruzi infection. The first reported occurrence of triatomine bugs in urban Sao Paulo was in 1988. The specimen, which was captured in Jardim Sao Luiz district, was from the genus Panstrongylus and was registered as Panstrongylus sp. but was not sexed. Since this first recorded occurrence, the following species have been found in the city: Panstrongylus geniculatus (2 occurrences), P. megistus (15 occurrences), Triatoma infestans (1 occurrence) and T. sordida (3 occurrences). In this paper, the importance of reporting occurrences of triatomine bugs in the city of Sao Paulo, one of the largest metropolis in the world, is discussed with an emphasis on P. megistus. The occurrences discussed here indicate the importance of entomological surveillance for these vectors even in urban centers although the possibility of vector transmission of Chagas disease in these centers is very low.
Keywords: Hemiptera; Reduviidae; Triatominae species; Entomological surveillance; Urban center; Trypanosoma cruzi; Chagas disease